Heterogeneous solar photo-fenton degradation of reactive Black 5 using foundry sand and fly ash: value addition to waste - Rajput, Himadri; Verma, Anoop; Kaur, Manpreet; Kaur, Taranjeet; Toor, Amrit Pal (Journal of Environmental Engineering and Landscape Management, 2016)
This work evaluates the scope of alternative sources of iron i.e. Foundry Sand (FS), Fly Ash (FA) and mixture of FS and FA in heterogeneous photo-Fenton process for the degradation and decolourization of the dye Reactive Black5 (RB5). SEM-EDS characterization of FS and FA confirmed the presence of iron and aluminium which are required for photo-Fenton. In case of FS as an iron source, results confirmed the degradation and decolourization efficiency of 90% in 70 min and 45 min respectively when the reaction parameters were H2O2 = 2.2 mm, FS dose = 0.5 g, ph 3. With FA 90% degradation was achieved within 30 min and 93% decolourization rate within 15 min. When a mixture of FS (0.1 gm) and FA (0.05 gm) is used as source of iron 99% degradation and decolourization of the dye was achieved under the reaction conditions where H2O2 = 2.2 mm, FA:FS = 1:2, ph 3.